PTU-091 Grading oesophageal varices in clinical practice: an inter-rater reliability study using high resolution endoscopy recordings. (17th June 2017) - Fateen, W; Sami, SS; Ragunath, K; Wilkes, EA; James, MW; Ortiz-Fernaćndez-Sordo, J; White, JR; Khanna, A; Coletta, M; Samuel, S; Aithal, GP; Guha, IN
Abstract : Introduction: Variceal size is a major predictor of the risk of bleeding in patients with liver cirrhosis. Guidelines from the American Association for the Study of the Liver (AASLD) recommend the use of a simplified system (small vs large) for grading of oesophageal varices (OV), but data on the reliability of this system compared to the conventional 3- grade classification remains lacking. We aimed to assess inter-rater reliability of these two widely used grading systems for OV. Method: High-resolution endoscopy recordings of 108 patients (n=8 training cohort and n=100 evaluation cohort) with chronic liver disease were prospectively collected using standardised criteria. Nine Gastroenterologists of variable experience performed independent evaluations of the videos in a random order. The cases were scored according to the presence or absence of OV. If OV were present they were scored using a 2-grade system (small and large) as well as a 3-grade system (small, medium and large). Overall agreement was analysed using intraclass correlation coefficient or kappa statistic as required. Results: Agreement on the presence or absence of varices was good (k=0.6, p<0.001). Agreement between observers using the 2-grade (0.74, 95% Confidence interval (CI) 0.68–0.80) was very similar to that using the 3-grade scoring system (0.76, 95% CI 0.70–0.81). The agreement between experts (2-grade: k=0.78, 95% CI 0.71–0.84 and 3-grade: k=0.79, 95% CI 0.72–0.84) was slightly higher than that between trainees (2-grade: k=0.7, 95% CI 0.61–0.77 and 3- grade: k=0.72, 95% CI 0.637–0.792). The agreement between observers and the reference endoscopist was slightly higher for the 2-grade system (k=0.55, p<0.001) in comparison to the 3-grade system (k=0.47, p<0.001). Conclusion: Observers had a good to substantial level of agreement using 2 different scoring systems of OV. We conclude that the simpler 2-grade system recommended by AASLD appears to be equivalent to the 3-grade system in terms of inter-observer agreement. This is the first study to support its use in clinical practice. Disclosure of Interest: None Declared